2019
DOI: 10.3390/en12234515
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Jeju Island Power System with an Offshore Wind Farm Applied to a Diode Rectifier HVDC

Abstract: The Jeju Island power system consists of two-unidirectional high voltage direct current transmission systems (HVDC), thermal power plants, and renewable energy sources. The local government’s policy states that a 100 MW offshore wind farm should be constructed in the future. Due to the small size and sensitivity of the Jeju Island power system, power system analysis must be carried out before the installation of the new facility. Therefore, the objective of this study was to analyze the Jeju Island power syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The study in [24] proposed the installation of a diode rectifier HVDC (DR-HVDC) for the new offshore wind farm (OWF) in the Jeju Island power system. The outcomes of this study revealed that the power system in steady and transient states is more stable, and the application of the DR-HVDC reduces costs and increases the reliability of an OWF compared to a conventional HVDC.…”
Section: Introductionmentioning
confidence: 99%
“…The study in [24] proposed the installation of a diode rectifier HVDC (DR-HVDC) for the new offshore wind farm (OWF) in the Jeju Island power system. The outcomes of this study revealed that the power system in steady and transient states is more stable, and the application of the DR-HVDC reduces costs and increases the reliability of an OWF compared to a conventional HVDC.…”
Section: Introductionmentioning
confidence: 99%